Atlas of Athenian inscriptions: a book of drawings of writings and writings on drawings - Avramidis, Konstantinos (The University of Edinburgh, 2018)
This thesis proposes a critical exchange between architecture and graffiti. Graffiti in Athens plays a key role in the expression of Greek tensions making this city an ideal place for developing such an exchange. The author acts in a three-fold manner in this research: as architectural designer, one with an impulse to survey by drawing and capable of grasping the matrix of the surfaces upon which graffiti finds an expression; as graffiti writer, somebody with some practical experience as graffitist hence partially equipped to decode the graffiti matrix placed on any given architectural matrix; and as writer on graffiti, who is interested in bringing together and working between the architectural and graffiti matrices to reveal their convergences, deviations and interdependences, and, in so doing, expose the hidden spatiality of graffiti writing. Stemming from this peculiar triple positioning, this book promotes a new situating of Athenian inscriptions. The thesis is presented as an Atlas of Athenian Inscriptions, a book of drawings of writings and writings on drawings. The Atlas offers, in both drawn and written form, a close study of four situations in which graffiti has been recorded. The thesis regards a recent significant graffiti Exhibition – in which the author is actively implicated by being invited into it as a graffiti writer and writer on graffiti – as a starting point, as its situation zero. By de-situating graffiti from its original urban and political context whilst placing it onto the gallery surfaces, this thesis argues that the Exhibition undermines graffiti’s critical potency and has transformed graffiti into an aesthetic object. However, perhaps paradoxically, presenting graffiti as an empty gesture, the Exhibition nonetheless raises questions concerning the situating role of graffiti. By including it in the Atlas together with the following more overt surface ruptures in political edifices, the Exhibition is framed as an equally political situation. The other three situations, all in Athens’ city centre, reflect three important periods in local political history and are emblematic in that they are the epicentres of historical ruptures during which they are extensively graffitied: the former Nazi Detention Centre which operates during the Axis occupation (1941-1944); the Athens Polytechnic that plays a pivotal role in the student uprising against the Greek Military Junta (1967-1974); and the Bank of Greece HQ building which is a site of recurring political expression in contemporary crisis (2010-2015). The Atlas indexes graffiti and related information from the city of Athens, the systematic organisation of which creates different graffiti-related matrices allowing us to make sense of, navigate in and reconstruct the Athenian graffiti landscape through characteristic surface environments. By placing different political situations in the same set with the Exhibition, the thesis aims to give critical voice to how graffiti is perceived. By resituating (graffiti) images, the Atlas restores broken and creates new links between them and their surfaces whilst revealing not only the spatiality of graffiti in Athens but also the spatiality of architecture of Athens as a recurring tension between the matrices of dissensus and consensus. The thesis deconstructs the mythology that architecture represents consensus and graffiti dissensus, since each is embedded in the other. Ultimately, by carefully considering graffiti’s situating character and graphic articulation, this research promotes rupture to the smoothing of its political asperity attempted by architecture, institutions and those writing on graffiti that seek to restrain it.
Keywords: architecture; graffiti; Athens; interdependence; de-situating graffiti; role of graffiti; local political history; political expression